Nutrient and Energy Balance, and Amino Acid Digestibility in Broilers Fed Canola Meal and an Exogenous Enzyme Combination - Araujo, Robert Guaracy Aparecido Cardoso [UNESP]; Vela, C. G.; Sartori, J. R. [UNESP]; Trindade Neto, M. A. (FapUNIFESP (SciELO), 2024)
The apparent total tract digestibility (ATTD; trial 1) and the apparent (AID) and standardized (SID) ileal digestibility of the amino acids (AA) (trial 2) in canola meal (CM) were evaluated with the addition of exogenous multi-carbohydrase (MC) and phytase (Phy). A total of 80 28-day-old broilers were allotted in a completely randomized design to receive treatments up to 35 days of age. A 2 × 2 factorial design was used to determine the enzyme effects on the ATTD of dry matter, nitrogen, calcium, phosphorus and fibre; as well as energy use and the AID and SID of AA, in five replicate cages. Supplementation with exogenous enzymes showed a positive interaction (p<0.05) between MC and Phy for nitrogen and energy. The isolated inclusion of Phy or MC showed a favorable effect (p<0.05) for dry matter, calcium, phosphorus and fiber. The enzyme inclusion on the AID and SID of AA in CM, established by comparing the means, suggested a better response to the addition of MC or Phy. Supplementation with Phy or MC was shown to be a viable alternative to increase the ATTD of nutrients and energy. The isolated inclusion of Phy or carbohydrate resulted in higher apparent and standardized digestibility of AA from CM.
Keywords: Amino acid digestibility; broiler chicks; canola meal; multi-carbohydrases; phytase